Acúmulo de graus-dia e duração do ciclo para cultivares de trigo em diferentes épocas de semeadura - Noreto, Lorena Maia (2013)
The objective of this study was to determine the growing degree-days sum and the relationship between the period length from sowing to physiological maturity and sowing dates of thirteen wheat cultivars, in the Palotina PR and Cascavel - PR. The data on wheat crop were colected by the Cooperativa Central de Pesquisa Agrícola (COODETEC) and correspond to the harvests of 2006 to 2011. The treatments consisted of 13 wheat cultivars, 3 sowing dates for Cascavel and 4 sowing dates for Palotina. The data used for the analysis were: Total elapsed days from sowing to the silking and to physiological maturity, and of the silking to physiological maturity, along with the growing degree-days sum for these periods, beyond grains yield and hectoliter weight. The results indicate that the average length of sowing to silking was 64 days for Palotina and 71 days for Cascavel. For the period from silking to physiological maturity the average length was 56 days for Palotina and 54 days for Cascavel. The increase in length of time from sowing to silking in cultivars sowed in May 25th (JD 145) was due to the decrease in air temperature. The average of growing degree-days sum between the period from sowing to physiological maturity was 1487, for both locations. The cultivars that stood out presenting a shorter period of silking to physiological maturity and high productivity were the cultivars CD 114, CD 120 and CD 124 for Palotina and CD 114, CD 120, CD 121, CD 122, CD 124 and Onix for Cascavel